Escherichia coli Promotes Endothelial to Mesenchymal Transformation of Liver Sinusoidal Endothelial Cells and Exacerbates Nonalcoholic Fatty Liver Disease Via Its FlagellinSummary - Bo Shen; Tianyi Gu; Zhenyang Shen; Cui Zhou; Yuecheng Guo; Junjun Wang; Binghang Li; Xianjun Xu; Fei Li; Qidi Zhang; Xiaobo Cai; Hui Dong; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2023)
Background＆Aims: Gut bacteria translocate into the liver through a disrupted gut vascular barrier, which is an early and common event in the development of nonalcoholic fatty liver disease (NAFLD). Liver sinusoidal endothelial cells (LSECs) are directly exposed to translocated gut microbiota in portal vein blood. Escherichia coli, a commensal gut bacterium with flagella, is markedly enriched in the gut microbiota of patients with NAFLD. However, the impact of E coli on NAFLD progression and its underlying mechanisms remains unclear. Methods: The abundance of E coli was analyzed by using 16S ribosomal RNA sequencing in a cohort of patients with NAFLD and healthy controls. The role of E coli was assessed in NAFLD mice after 16 weeks of administration, and the features of NAFLD were evaluated. Endothelial to mesenchymal transition (EndMT) in LSECs induced by E coli was analyzed through Western blotting and immunofluorescence. Results: The abundance of gut Enterobacteriaceae increased in NAFLD patients with severe fat deposition and fibrosis. Importantly, translocated E coli in the liver aggravated hepatic steatosis, inflammation, and fibrosis in NAFLD mice. Mechanistically, E coli induced EndMT in LSECs through the TLR5/MYD88/TWIST1 pathway during NAFLD development. The toll-like receptor 5 inhibitor attenuated E coli–induced EndMT in LSECs and liver injury in NAFLD mice. Interestingly, flagellin-deficient E coli promoted less EndMT in LSECs and liver injury in NAFLD mice. Conclusions: E coli promoted the development of NAFLD and promoted EndMT in LSECs through toll-like receptor 5/nuclear factor kappa B–dependent activation of TWIST1 mediated by flagellin. Therapeutic interventions targeting E coli and/or flagellin may represent a promising candidate for NAFLD treatment.